PENGEMBANGAN MEDIA KOMIK DALAM PEMBELAJARAN MEMBACA BAHASA INDONESIA SEHATLAH RAGAKU UNTUK SISWA SD DENGAN APLIKASI PIXTON - Resyi Abdul Gani; Widi Sukmawati, Adinda; Budiana, Sandi; Hikmah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop and determine the feasibility of comic media in learning to read Indonesian with the Pixton application as well as to find out how teachers and students respond to the development of comic media assisted by the Pixton application. The research method used in this study is the Research and Development (R&D) development model with the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. This research was carried out SDN Loji 2 with a class IV research subject. Based on the results of validation by media experts, the product validity score was 92% with very feasible criteria, the validation results by linguists obtained a validity score of 100% with very feasible criteria, and the validation results by material experts obtained a validity score of 92% with very feasible criteria. The comic media with the Pixton application is very valid and the media is suitable to be tested on teachers and students in the classroom. Based on the results of the trial through the response questionnaire, the teacher got a score of 88% and the results of the trial through the student response questionnaire got a response score of 87.4% with the category of very feasible. Based on the results of the two trials, it can be concluded that the comic media assisted by the Pixton application is very valid and very good to use in learning Indonesian.